Demografischer Wandel und Industrie-Qualifikationsrahmen Logistik - Hella Abidi; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2014)
– The purpose of this research is to investige the impact of the demographic change on the logistics industry in Germany. In order to explore this with a better understanding of the impacts of demographic change on the overall competence situation in Germany, a simulation based on a competence survey from 2012 with 1,068 logistics employees is used. This shows the effects of aging working-age cohorts on the competence allocation in the German logistics workforce - but quite huge impacts on the total available knowledge pool mainly due to the decrease of available people within the total workforce. Furthermore we use the Industry Qualification Framework (IQF) Logistics as an instrument to mitigate the ensuing lack of employability in the German and European logistics industry. These results shall inspire further research and hands-on strategic management concepts to tackle questions of lifelong learning as well as migration and integration in the German logistics workforce.
Keywords: 650